2013
DOI: 10.11646/zootaxa.3694.4.1
|View full text |Cite
|
Sign up to set email alerts
|

On some taxonomically confused species of the genus Amphiesma Duméril, Bibron & Duméril, 1854 related to Amphiesma khasiense (Boulenger, 1890) (Squamata, Natricidae)

Abstract: Three species of the genus Amphiesma Duméril, Bibron & Duméril, 1854 have long been confused in the literature, with each other and with other species of the genus. Amphiesma khasiense (Boulenger, 1890) has been considered to inhabit a large geographical region, extending from northeastern India, east to Vietnam and southern Thailand. Amphiesma boulengeri (Gressitt, 1937) has been regarded as a species endemic to southeastern China. Amphiesma inas (Laidlaw, 1901) has been recorded from West Malaysia, Thailand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…We also corroborate the findings of David et al (2013) and Guo et al (2014), who reported variation suggestive of additional unrecognized species diversity under the names H. boulengeri and H. venningi, the latter of which is polyphyletic in Guo et al (2014) and herein. Stuart et al (2006) suggested that there are no "geographically widespread, forest-dwelling frog species in Southeast Asia. "…”
Section: Discussionsupporting
confidence: 91%
“…We also corroborate the findings of David et al (2013) and Guo et al (2014), who reported variation suggestive of additional unrecognized species diversity under the names H. boulengeri and H. venningi, the latter of which is polyphyletic in Guo et al (2014) and herein. Stuart et al (2006) suggested that there are no "geographically widespread, forest-dwelling frog species in Southeast Asia. "…”
Section: Discussionsupporting
confidence: 91%
“…In this work, it is not our main aim to explore and address species level taxonomy, but several species are apparently non-monophyletic, and should be examined in future studies. Previously, morphological work indicated that some species of Amphiesma sensu lato were poorly diagnosed and quite variable, contributing to frequent misidentification and confusion between these species (David et al 2007(David et al , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Field surveys were conducted in the Xuan Lien Nature Reserve by C. T. Pham Taxonomic identification of the specimens were made mainly based on the following literature: Gressit (1937) [4], Smith (1943) [20], Schulz (1996) [19], Orlov et al (2004) David et al (2013David et al ( , 2015b [1,3]. For common names, we followed Nguyen et al (2009) [13] …”
Section: Methodsmentioning
confidence: 99%
“…In Vietnam, this species is known from Ha Tinh, Quang Binh, Quang Tri, Thua Thien Hue, Da Nang, and Kon Tum provinces [3]. Elsewhere, this species is recorded from Laos [3].…”
Section: Hebius Boulengeri (Gressitt 1937)mentioning
confidence: 96%
See 1 more Smart Citation